Removing PEG tubes with 'buried bumpers': Lessons learnt from four patients. Issue 2 (April 2015) - Berry, Philip; Langlands, Sarah; Campbell, Claire; Direkze, Natalie; Ala, Aftab; Karat, Isabella; Keeling, Peter; Taylor, Jeremy
Summary: We noted an increase in the number of presentations with dysfunctional PEG tubes due to the 'buried bumper syndrome' (BBS). There is no standard approach to this problem, although case reports exist of endoscopic needle knife excision and forceful pulling. We present a description of our experience in the management of this problem and the lessons learnt by complications or adverse outcomes. Two patients died within 2 weeks of endoscopic therapy. Successful and safe endoscopic removal appears dependent on the depth of the bumper, and this may be gauged by whether or not a wire can be inserted into the gastric lumen via the external portion of the tube. Further experience with radiological estimation of depth is required. The underlying frailty of this group of patients requires careful pre-intervention risk assessment and may favour a conservative approach.